Litter pattern over sand dunes of Aravalli forest at Ajmer (Rajasthan) - Sharma, Beena (Journal of Phytology, 2012)
The sand dunes at Ajmer (Rajasthan) selected for the investigation i.e. Pushkar valley base (dominated by A.tortilis), Leela sewri (dominated by A.sengal) and Pachkund (dominated by Eucalyptus camaldudensis) are situated in 48sqkm area in the North-West foot hills of Nagpahar, a prominent mountain belt of central Aravallis. Stabilized sand dunes of Ajmer are different in respect of quantity and quality of litter production. Except for Pachkund the other two sand dunes i.e. Leela sewri and Pushkar valley base have low stature and scattered distribution of trees, therefore, production of litter in these sites is comparatively low than heavily vegetated sand dunes. Maximum litter fall takes place from March to April under each plantation. A decrease in amount of litter was observed up to August. When individual tree species are considered, E. camaldulensis was by far the greatest producer of litter followed by A. tortilis and A.senegal. The Pachkund area, which received comparatively very high litter, showed complete stabilization with characteristic soil conditions. While the other two sites receive very low amount of litter are comparatively less stabilized and some times a major area is converted in to active dune during the summers, such dunes are partially stabilized only during the rainy season. It may be concluded that both moisture and litter play an important role in the process of stabilization.